Population survey of elephants in Okwangwo Division, Cross River National Park, Nigeria - Obot, Emmanuel; Edet, Clement; Ogar, Gabriel; Ayuk, Joy (Pachyderm, 2005)
A elephant census based on dung counts along five trails, with a total length of 139 kms, was undertaken March 1997-May 1998 in Cross River NP, Nigeria. ’There appears to be a seasonal local migration of this population between Cross River NP and the neighbouring Takamanda FR in Cameroon: the elephants spend most of the rainy season in Cameroon and the dry season in Cross river NP.’ Within the park elephants seem to occupy a home range of about 239 sq km, from Okwangwo in the centre of the park through Bamba on the eastern boundary to Bashu on the south, and dung count analysis suggests 74 animals in this area. This study indicates 50 to 130 elephant are in the area, and interviews with hunters suggest there are about 10 groups of around 15 animals per group. This latter figure suggests 150 animals in total which compares favourably with the study maximum estimate of 130. Authors note poaching for ivory and meat was excessive before the park was gazetted in 1991, and antipoaching activities must be maintained if any population is to survive.